Prvi uredniki Slovenskega naroda - Globočnik, Damir (Teorija in praksa, 2018)
In the early years of being published, the Slovenski narod (Slovenian Nation) newspaper played a part in the life stories of three editors and several other personalities who would go on to earn mention in Slovenian cultural and political historical overviews. The newspaper was founded by patriots from Slovenian Styria, while the course of its programme was set out by Dr Janko Srnec based on Fran Levstik's outline. Its final form was defined by its first editor Anton Tomšič, a legal secretary at the office of Mariborbased attorney Dr Ferdinand Dominkuš. Josip Jurčič helped Tomšič in his work as an editor. His radical editorial style saw Tomšič become entangled in a number of lawsuits triggered by Levstik's hard-hitting articles (in 1868 and 1869). In 1870, pressured by the owners of Slovenski narod, Tomšič publicly denounced Levstik's satirical paper Pavliha, becoming the main reason for its termination. In May 1871, Tomšič died in mysterious circumstances. In the three months following his death, Slovenski narod was edited by interning notary Ivan Železnikar, after which the Styrian Young Slovenians entrusted the job to Josip Jurčič. In 1871, the Young Slovenians established a printing press in Maribor and tried publishing a satirical paper entitled Sršeni (Hornets) with Železnikar as the editor (only two issues were ever published). In January 1882, Železnikar became the editor of Slovenski narod.
Keywords: Cultural history; Editors; Jurčič, Josip; Kulturna zgodovina; Political history; Politična zgodovina; Slovenian newspapers; Slovenski časniki; Slovenski narod (periodična publikacija); Tomšič, Anton; Uredniki; Železnikar, Ivan